Invisible Hands Behind the Algorithm: Cyber Exploitation and Child Labour in Hotel Supply Chains - Ms. Juhi Naseem; Prof. (Dr.) Gurmeet Singh (Kurdish Studies, 2025)
The digital transformation of the hospitality sector has introduced algorithmic management systems that optimize efficiency, cost, and labour allocation across hotel supply chains. However, beneath this technological advancement lies an emerging form of exploitation, algorithmic complicity, where automated systems inadvertently enable or conceal the use of child labour in outsourced services such as housekeeping, laundry, and catering. This research examines how artificial intelligence (AI) and digital procurement platforms contribute to cyber exploitation by prioritizing productivity and profit over ethical labour compliance. Employing a doctrinal, analytical, and qualitative methodology, the study analyses relevant Indian and international legal frameworks, including the Child Labour (Prohibition and Regulation) Act, 1986, the Information Technology Act, 2000, and ILO conventions, alongside corporate digital governance standards. The findings reveal critical regulatory and ethical gaps in algorithmic accountability, highlighting how opaque AI systems obscure violations in multi-tiered hotel supply chains. The paper concludes by recommending algorithmic transparency laws, blockchain-based auditing, and mandatory digital due diligence to ensure ethical labour practices and prevent technology-driven exploitation in the hospitality industry.